The narratives of racism, trauma, slavery and resilience: a comparative analysis of Toni Morrison’s The Bluest Eye and Beloved - Islam, Attin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.